PHYTOCHEMICAL CHARACTERIZATION AND ANTIOXIDANT ACTIVITY OF THE NORTHERN MOROCCAN SPECIES: WITHANIA FRUTESCENS L. - ABDELFATTAH EL MOUSSAOUI; FATIMA ZAHRA JAWHARI; DALILA BOUSTA; AMINA BARI (Asian Journal of Pharmaceutical and Clinical Research, 2019)
Objective: In this study, we were interested in qualitative, quantitative phytochemical characterization and evaluation of the antioxidant capacity of the total extracts of a plant from northern Morocco, the species selected for this study is Withania frutescens. Materials and Methods: Analysis of mineral elements by inductive coupling plasma-atomic absorption spectroscopy (ICP-AES), phytochemical screening, polyphenol and tannin assays, evaluation of antioxidant activity by the 1,2-diphenyl-β-picrylhydrazyl (DPPH) free radical scavenging method and reducing power. Results: The plant contains alkaloids, saponins, tannins, mucilages, and coumarins. It has a relatively high content of total polyphenols and tannins of 19.53±0.018 μg genetic generalized epilepsy/mg MS and 6.258±0.062 μg Eqcat/mg MS, respectively. The analysis of mineral elements by ICP-AES shows that our species is rich in mineral elements which are calcium, magnesium, and sodium, and it is devoid of metallic elements such as nickel, lead, cadmium, and cobalt. The evaluation of antioxidant activity by the DPPH free radical scavenging method shows that the half maximal inhibitory concentration of the tested extracts has an antiradical activity of about 0.056±0.008 μg/ml for the ethanol extract and 0.213±0.004 μg/ml for the methanol extract compared to the butylated hydroxytoluene value of 0.009±0.0004 μg/ml which was used as a reference. The reducing capacity test shows that methanolic extract has a high antioxidant capacity (0.213±0.006) compared to ethanolic extract (0.043±0.004) but remains low compared to ascorbic acid (0.003±0.0004) which was used as reference. Conclusion: Phytochemical analysis of W. frutescens shows that this plant is rich in high quantities of alkaloids, saponins, mucilage, tannins, and coumarins. It contains an average amount of total polyphenols and tannins that confer significant antioxidant activity to the plant studied.